2020
DOI: 10.1007/s00415-020-09998-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review of burden of illness in chronic inflammatory demyelinating polyneuropathy (CIDP)

Abstract: Background Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare neurological disorder characterised by muscle weakness and impaired sensory function. The present study provides a comprehensive literature review of the burden of illness of CIDP. Methods Systematic literature search of PubMed, Embase, and key conferences in May 2019. Search terms identified studies on the epidemiology, humanistic burden, current treatment, and economic burden of CIDP published since 2009 in English. Results Forty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 57 publications
(247 reference statements)
0
42
0
1
Order By: Relevance
“…According to one study, 17% and 74% of patients with CIDP reported severe pain and severe fatigue, respectively [ 12 ]. Another study reported impairments in daily activities like unzipping, using a knife and fork, and requiring some support for outdoor activities like walking and standing [ 13 ]. This case illustrates diagnostic complexity and poor response to treatment due to prolonged ICU stay leading to ICU myopathy and deconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…According to one study, 17% and 74% of patients with CIDP reported severe pain and severe fatigue, respectively [ 12 ]. Another study reported impairments in daily activities like unzipping, using a knife and fork, and requiring some support for outdoor activities like walking and standing [ 13 ]. This case illustrates diagnostic complexity and poor response to treatment due to prolonged ICU stay leading to ICU myopathy and deconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic plasma exchange (PLEx) may provide an alternative therapy for patients who do not respond to IVIg and corticosteroids; it can be very effective, especially in patients who have a relapsing disease course or with severe relapses [77,78]. A PLEx course of 5-10 every-other-day sessions within 2-4 weeks is commonly used [9].…”
Section: Plasma Exchange and Immunoadsorptionmentioning
confidence: 99%
“…A PLEx course of 5-10 every-other-day sessions within 2-4 weeks is commonly used [9]. Several small trials have shown that between 48 and 81% of CIDP patients have significant short-term improvement after PLEx, but rapid deterioration may occur after completion of treatment [77,79].…”
Section: Plasma Exchange and Immunoadsorptionmentioning
confidence: 99%
“…Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a chronic and disabling disease with a range prevalence of 0.8-8.9 cases per 100,000 and incidence of 0.2-1.6/ 100,000 [1]. It is the most frequent acquired immunemediated chronic neuropathy and has a broad spectrum of possible clinical presentation including typical and atypical forms [2][3][4].…”
Section: Introductionmentioning
confidence: 99%